1992
DOI: 10.1007/bf00198936
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous rhythms and chaos in crassulacean acid metabolism

Abstract: Endogenous free-running regular circadian oscillations of net CO2 exchange in the crassulacean-acidmetabolism (CAM) plant Kalanchoë daigremontiana Hamet et Perrier de la Bâthie under constant external conditions in continuous light have been shown to change to irregular non-predictable (chaotic) time behaviour as irradiance or temperature are raised above a critical level. A model of CAM has been constructed with pools of major metabolites of varying concentrations, flows of metabolites leading to exchange bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 26 publications
2
71
0
1
Order By: Relevance
“…Some authors have observed chaotic dynamics in plants in different physiological processes. Lüttge and Beck (1992) showed the possible existence of chaotic dynamics in endogenous rhythms in certain CAM species. Krempaský et al (1993) indicated that varying light intensities caused changes in the patterns of photosynthetic temporal behaviors, ranging from periodic to chaotic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have observed chaotic dynamics in plants in different physiological processes. Lüttge and Beck (1992) showed the possible existence of chaotic dynamics in endogenous rhythms in certain CAM species. Krempaský et al (1993) indicated that varying light intensities caused changes in the patterns of photosynthetic temporal behaviors, ranging from periodic to chaotic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Lüttge & Beck (1992) mostraram a possível existência de dinâmica caótica no ritmo circadiano em espécies com metabolismo ácido crassuláceo (MAC). Krempasky et al (1993) mostraram que, alterando a intensidade luminosa, podem surgir padrões temporais no comportamento do sistema fotossintético variando de periódico a caótico.…”
Section: Complexidade Em Fisiologia E Bioquímica De Plantas: Caminhosunclassified
“…Endogenous oscillators of living cells and organisms are based on feedback loops in complex biochemical-reaction networks. Crassulacean acid metabolism (CAM) is a specific mechanism of inorganic carbon acquisition for photosynthesis [1,2]. CAM plants take up external CO 2 during the night while the stomata are open.…”
Section: Introductionmentioning
confidence: 99%
“…The CO 2 is fixed in the plant in the form of organic acids, normally malate, via the enzyme phosphonenolpyruvate carboxylase (PEPc) and stored overnight in the vacuole [3]. The malic acid is accumulated to high concentrations of up to several hundred millimolars and stored in the cell sap vacuole [1,2]. During the daytime, malate is remobilized from the vacuole and decarboxylated again [3].…”
Section: Introductionmentioning
confidence: 99%